Solutions to gas lift optimisation of oil wells with high water-cut in Cuu Long basin - Nguyen Hai An (Petrovietnam Journal, 2019)
Artificial gas lift is frequently used in secondary recovery to boost the production rate of mature oil fields, especially in areas with high water-cut and suspended solids. The high water-cut of production stream may require large amount of gas for lifting a unit volume of crude. In addition, the production operation is costly because the ratios of water/oil become higher and oil production rates decline dramatically. To maximise the economic return of oil production, it is important to into account the cost of lift gas injection (including recompression costs), the sale price of oil and gas, other production costs, the money discount rate and the rate of inflation. In this paper, the net cash flow of the field is maximised, then decisive parameters will be adjusted over the production life of the field by allocating the flow rate of injected gas to each production well.